Trigger factors of using Moodle or e-learning by faculty of Medicine and health Sciences College and Education College - Saida Affouneh; Eman Alshawish (Universitas Pendidikan Ganesha, 2022)
There are several obstacles to implementing e-learning. This study aims to identify barriers and facilitators in using Moodle or e-learning by the Faculty of Medicine and Health Sciences, the College of Health Sciences, and the College of Education. This type of research is qualitative research. This research report is based on the SRQR guidelines. The sample used in this study amounted to seven Faculties of Medicine and Health Sciences, Colleges, and Schools of Education. The method used in collecting data interviews. The instrument used in data collection is an interview sheet. The technique used in analyzing the data is descriptive qualitative analysis. The result of this research is that the study reveals three key factors that represent barriers to using Moodle or e-learning from the participants' perceptions. First, individual barriers (educators & students). Second, institutional barriers or workplace barriers. Third, the participants considered the use of social media (Facebook) in the teaching process unprofessional at the academic level. The English competence of Medical and Health Science students is considered the central supporting factor in using e-learning compared to education students. Participants considered the use of Facebook as unprofessional in academic level communication.